Syaḥrûr Subjective Hermeneutic Controvertion of Non-Marital Marriage Interpretation - Nur Khalis (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
In modern reality, exist an intersection between hermeneutic applications based on the motivation of war and peace. The existence of subjective hermeneutics is identical as a breakdown in every difference but the fact that it raise chaos ignores the interpretation of synonymity change into regressive sophistic interpretation. The purpose of this research is to place subjective hermeneutics as a study of the free interpretation of sophia claims discipline (wise) with the assumption that it gives birth to renewable ethical polarization and also progressive. This research is a library that is used to answer specific problems directly that raises the perspective of truth claims of interpretation that is different from the old interpretations. The results showed that subjective hermeneutics should conciliate collaborations of narrative (haggadic interpretations), prescribed ways of life (halakhic rules) and (meaningholders of early texts (masoretic sources). But subjective hermeneutics propagates authoritative hermeneutics that distinguishes between original (competent) meanings and non-original (non-competent) meanings. Syaḥrûr through subjective hermeneutics uses perversion (taḥrîf method) from the word in Qur’an such as lawful ownership (milk yamîn), solemn convenant (mîthâq), adultery (zinâ) and illegal sexual intercouse (fawâḥiṡ) to initiate non-marital marriages.